Surface protrusion induced by inter-diffusion on Cu-Sn micro-pillars. (December 2022) - Chen, Yang; Dai, Wenjie; Liu, Yingxia; Chen, Chih; Tu, K.N.; Chen, Guang
Graphical abstract: Highlights: A unique 2-step sidewall Cu3 Sn IMC formation around Cu-Sn micro-pillars is first revealed. The low nucleation barrier for sidewall Cu3 Sn is proved by density functional theory. A kinetic model is proposed to predict the mean lateral growth rate of the sidewall IMC. Abstract: With downward scaling of the micro-bumps in three-dimensional integrated circuits, surface inter-diffusion becomes dominant, changing the kinetic path of intermetallic compounds (IMC) formation and causing serious reliability issues. However, an in-depth understanding of the surface inter-diffusion process and the corresponding influence on the formation mechanism of IMC in a micro-bump remain unclear. We conducted annealing at 170 ℃, over 16 h for pillar type Sn/Cu micro-bumps and observed a unique 2-step sidewall Cu3 Sn IMC formation phenomenon on the FIB-cut clean surface of the micro-bumps. It is found the two-step sidewall IMC formation is dominated by the surface inter-diffusion of Sn and Cu atoms. Density functional theory calculations reveal that the activation energy barrier of nucleation for sidewall Cu3 Sn IMC is about 1/3 of that of sidewall Cu6 Sn5 on corresponding interfacial IMC layers, making the formation of sidewall Cu3 Sn dominant. Moreover, we proposed a kinetic model that can predict the mean lateral growth rate of the sidewall IMC which may cause fatal short-circuit failure.